Domingo Del Monte collection of Spanish colonial history - Del Monte, Domingo, 1804-1853.
Correspondence, diaries, writings, reports, official documents, and printed material, collected or written by Del Monte, relating to the Spanish colonial history of Cuba, Mexico, Peru, South America, and the West Indies. Includes material on copper mines, Yucatan insurrection of 1825, Cuban regulation of labor and immigration, slavery and the condition of blacks in Cuba, slavery in the West Indies and the Philippines, and the slave trade.
Cuban historian. Full name: Domingo Del Monte y Aponte.
Collection material in Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blacks -- Cuba; Copper mines and mining -- Latin America; Emigration and immigration law -- Cuba; Labor laws and legislation -- Cuba; Slavery -- Cuba; Slavery -- Philippines; Slavery -- West Indies; Cuba -- History; Mexico -- History; Peru -- History; South America -- History; Spain -- Colonies -- America; West Indies -- History; Yucatán (Mexico : State) -- History -- 19th century; Historians